Evaluasi Penerapan Perhitungan Pajak Penghasilan Pasal 21 : Studi Kasus Pada Yayasan Mardi Wiyata - Lis Lestari Sukartiningsih; Galuh Budi Astuti ; Michael Andrean (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to evaluate the application of income tax calculations article 21 at the Mardi Wiyata Malang Foundation. This type of research is a case study, the research population is 429 permanent employees of the Mardi Wiyata Malang Foundation. Sample selection using the purposive sampling method selected 19 employees as the research sample. Quantitative descriptive data analysis techniques. The problem in this research is that the calculation, payment and reporting of income tax article 21 of the Mardi Wiyata Malang Foundation is not efficient because it makes deductions for PPh Article 21 that are too large. The proof is that the in-kind allowances provided by the Foundation are included in taxable allowances and there is a deduction for office fees amounting to IDR 10,798,573.00 - which exceeds the maximum limit for deductions for office expenses of IDR 6,000,000 in accordance with the Law on Harmonization of Tax Regulations. The cause of this problem is that the treasurer of the Mardi Wiyata Foundation, especially in the tax sector, does not understand the calculation of PPh Article 21 based on the HPP Law. As a result, Foundation employees experienced losses due to excessively large tax deductions. The results of quantitative descriptive analysis using the calculation of Income Tax Article 21 according to the HPP Law are more efficient.